2020
DOI: 10.1111/tme.12677
|View full text |Cite
|
Sign up to set email alerts
|

Association between HLA‐DRB1*01 and HLA‐DRB1*15 with alloimmunisation in transfusion‐dependent patients with thalassaemia

Abstract: BackgroundAlloantibody production is one of the most challenging complications in transfusion‐dependent thalassaemia patients. Haemolytic anaemia, an increase in blood consumption, difficulty in haematopoietic stem cell transplantation and reduced quality of life are consequences of alloimmunisation. The most predisposed antigens (Ags) for alloantibody development are Rh and Kell blood group Ags.ObjectiveThe aim of the present study is to evaluate any correlation between HLA‐DRB1 alleles and Rh and Kell alloan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…7 To distinguish the immunological response against epitopes of KEL, RhCE, and RhD proteins, we analyzed separately the three groups of patients who presented immune response against these RBC antigens, evaluating if the presence of the HLA-DRB1*15 allele predisposed the individual to an alloimmunization against specific proteins. The findings reinforced the positive relationship that this allele exerts on alloimmunization against antigens of Rh and Kell systems and may explain why it has often been associated with hyperresponders, especially patients with simultaneous anti-D + C. 21,22,31,32 Although related to the most frequent antibodies against RBC, the association with the HLA-DRB1*15 allele cannot be generalized as Jk a and Di a alloimmunizations were associated only with the HLA-DRB1*01 and *07 alleles, respectively. 17,19 Considering that the combined frequency of the haplotypes encompassing D and C antigens (DCcee = 34.4%, DCCee = 15.5%, DCcEe = 12%, DCCEe = 0.3%, and DCcEE = 0.3%) reached 62.5% in the Brazilian population, 33 one may assume that one of the reasons for observing the anti-D + C combination among pregnant women without a previous transfusion history is the high frequency of incompatible mother/fetus phenotypes.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…7 To distinguish the immunological response against epitopes of KEL, RhCE, and RhD proteins, we analyzed separately the three groups of patients who presented immune response against these RBC antigens, evaluating if the presence of the HLA-DRB1*15 allele predisposed the individual to an alloimmunization against specific proteins. The findings reinforced the positive relationship that this allele exerts on alloimmunization against antigens of Rh and Kell systems and may explain why it has often been associated with hyperresponders, especially patients with simultaneous anti-D + C. 21,22,31,32 Although related to the most frequent antibodies against RBC, the association with the HLA-DRB1*15 allele cannot be generalized as Jk a and Di a alloimmunizations were associated only with the HLA-DRB1*01 and *07 alleles, respectively. 17,19 Considering that the combined frequency of the haplotypes encompassing D and C antigens (DCcee = 34.4%, DCCee = 15.5%, DCcEe = 12%, DCCEe = 0.3%, and DCcEE = 0.3%) reached 62.5% in the Brazilian population, 33 one may assume that one of the reasons for observing the anti-D + C combination among pregnant women without a previous transfusion history is the high frequency of incompatible mother/fetus phenotypes.…”
Section: Discussionsupporting
confidence: 54%
“…To distinguish the immunological response against epitopes of KEL, RhCE, and RhD proteins, we analyzed separately the three groups of patients who presented immune response against these RBC antigens, evaluating if the presence of the HLA‐DRB1*15 allele predisposed the individual to an alloimmunization against specific proteins. The findings reinforced the positive relationship that this allele exerts on alloimmunization against antigens of Rh and Kell systems and may explain why it has often been associated with hyperresponders, especially patients with simultaneous anti‐D + C 21,22,31,32 . Although related to the most frequent antibodies against RBC, the association with the HLA‐DRB1*15 allele cannot be generalized as Jk a and Di a alloimmunizations were associated only with the HLA‐DRB1*01 and *07 alleles, respectively 17,19 …”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Several studies demonstrated that HLA-DRB1*15 was frequently present in multiple RBC antibody responders and might defi ne a high-responding phenotype (13)(14)(15). The other recent investigations confi rmed that the frequency of HLA-DRB1*15 was higher in the multi-responder group than in non-responders, which support the idea that HLA typing before transfusion could be helpful in reducing alloimmunization in chronically transfused patients (21,22).…”
Section: Discussionmentioning
confidence: 80%